Identification and Characterization of a Mandelamide Hydrolase and an NAD(P)(+)-Dependent Benzaldehyde Dehydrogenase from Pseudomonas putida ATCC 12633 - McLeish, Michael J. (American Society for Microbiology, 2003)
The enzymes of the mandelate metabolic pathway permit Pseudomonas putida ATCC 12633 to utilize either or both enantiomers of mandelate as the sole carbon source. The genes encoding the mandelate pathway were found to lie on a single 10.5-kb restriction fragment. Part of that fragment was shown to contain the genes coding for mandelate racemase, mandelate dehydrogenase, and benzoylformate decarboxylase arranged in an operon. Here we report the sequencing of the remainder of the restriction fragment, which revealed three further open reading frames, denoted mdlX, mdlY, and mdlD. All were transcribed in the opposite direction from the genes of the mdlABC operon. Sequence alignments suggested that the open reading frames encoded a regulatory protein (mdlX), a member of the amidase signature family (mdlY), and an NAD(P)(+)-dependent dehydrogenase (mdlD). The mdlY and mdlD genes were isolated and expressed in Escherichia coli, and the purified gene products were characterized as a mandelamide hydrolase and an NAD(P)(+)-dependent benzaldehyde dehydrogenase, respectively.